Transcriptome‐derived evidence supports recent polyploidization and a major phylogeographic division in Trithuria submersa (Hydatellaceae, Nymphaeales). Issue 1 (27th November 2015) - Marques, Isabel; Montgomery, Sean A.; Barker, Michael S.; Macfarlane, Terry D.; Conran, John G.; Catalán, Pilar; Rieseberg, Loren H.; Rudall, Paula J.; Graham, Sean W.
Summary: Relatively little is known about species‐level genetic diversity in flowering plants outside the eudicots and monocots, and it is often unclear how to interpret genetic patterns in lineages with whole‐genome duplications. We addressed these issues in a polyploid representative of Hydatellaceae, part of the water‐lily order Nymphaeales. We examined a transcriptome of Trithuria submersa for evidence of recent whole‐genome duplication, and applied transcriptome‐derived microsatellite (expressed‐sequence tag simple‐sequence repeat (EST‐SSR)) primers to survey genetic variation in populations across its range in mainland Australia. A transcriptome‐based K s plot revealed at least one recent polyploidization event, consistent with fixed heterozygous genotypes representing underlying sets of homeologous loci. A strong genetic division coincides with a trans‐Nullarbor biogeographic boundary. Patterns of 'allelic' variation (no more than two variants per EST‐SSR genotype) and recently published chromosomal evidence are consistent with the predicted polyploidization event and substantial homozygosity underlying fixed heterozygote SSR genotypes, which in turn reflect a selfing mating system. The Nullarbor Plain is a barrier to gene flow between two deep lineages of T. submersa that may represent cryptic species. The markers developed here should also be useful for further disentangling species relationships, and provide a first step towards future genomic studies in Trithuria .